(untitled) (Baghdad Science Journal, 2021)
Implementing smart community engagement should consider careful planning and collaboration with numerous stakeholders, including the community. The technology and program must be designed to frame its purpose and should link back to specific goals of implementing smart community engagement. Digital services do not guarantee a smart engagement between the community and the local government. This is the case for the Kubang Pasu local government where several online services have been provided in their attempt to implement the smart community concept. However, understanding on the preferences of features and requirements of existing web-based systems and the impact of these systems is lacking. Therefore, a perception study needs to be conducted to obtain information regarding smart community engagement implementation. This study aimed to discover the community’s perceptions on smart community engagement, specifically for Kubang Pasu in terms of its local context. To achieve this, a combination of interview and online survey was employed involving stakeholders of several organizations and 309 respondents among the community in Kubang Pasu. Result of the interview and survey revealed moderate engagement between the community and organizations due to low awareness, moderate engagement between the community and local authorities, low exposure to online services, as well as the weaknesses of the current online systems. It can be concluded that the satisfaction level of the respondents with officers at the organizations was only moderate. The implementation of e-services could reduce face-to-face interactions, which could help to improve the satisfaction level. This could also help in moving toward the smart community engagement concept. Therefore, the smart communication method via social media, email, and website could be employed to increase the low rating of public engagement with the authorities. This move will foster the prompt implementation of smart community engagement.